2018
DOI: 10.1186/s12877-018-1013-y
|View full text |Cite
|
Sign up to set email alerts
|

The decision-making process for unplanned admission to hospital unveiled in hospitalised older adults: a qualitative study

Abstract: BackgroundThe hazards of hospitalisation, and the growing demand for goal-oriented care and shared decision making, increasingly question whether hospitalisation always aligns with the preferences and needs of older adults. Although decision models are described comprehensively in the literature, little is understood about how the decision for hospitalisation is made in real life situations, especially under acute conditions. The aim of this qualitative study was to gain insight into how the decision to hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…A healthy patient may benefit from their ability to make their own decisions, while also offering relief to his/her caregiver and, thus, lessening their burden. These findings are consistent with a previous study that revealed unplanned admission was based upon a combination of factors including oneself, the family, and the physician [ 41 ]. Secondly, nearly half of the patients visiting EDs were experiencing cognitive impairment, with one third displaying symptoms of depression.…”
Section: Discussionsupporting
confidence: 93%
“…A healthy patient may benefit from their ability to make their own decisions, while also offering relief to his/her caregiver and, thus, lessening their burden. These findings are consistent with a previous study that revealed unplanned admission was based upon a combination of factors including oneself, the family, and the physician [ 41 ]. Secondly, nearly half of the patients visiting EDs were experiencing cognitive impairment, with one third displaying symptoms of depression.…”
Section: Discussionsupporting
confidence: 93%
“…Patients perceive optimal care as available, with continuity and adjusted to their needs (Bayliss et al, 2008 ). The decision to call for an ambulance is taken acutely by older patients or significant others (Van der Kluit et al, 2018 ). Factors leading to the decision are situations that cannot be self-handled and when no other choice exists (Booker et al, 2017 ; Van der Kluit et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Older people in this study also described a number of advantages of hospital not previously mentioned by GPs, 11 including the convenience of having assistance with everyday tasks, the security of regular monitoring and reduced burden and worry for family/caregivers compared with staying at home. These views are echoed in several existing qualitative studies exploring older patients views of a hospital stay in other European countries 23 24 and in the response of a survey of older patients in the USA. 25 …”
Section: Discussionmentioning
confidence: 94%